2006
DOI: 10.1186/1471-2164-7-166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis and integrative classification of NCI60 cell lines and primary tumors using gene expression profiling data

Abstract: Background: NCI60 cell lines are derived from cancers of 9 tissue origins and have been invaluable in vitro models for cancer research and anti-cancer drug screen. Although extensive studies have been carried out to assess the molecular features of NCI60 cell lines related to cancer and their sensitivities to more than 100,000 chemical compounds, it remains unclear if and how well these cell lines represent or model their tumor tissues of origin. Identification and confirmation of correct origins of NCI60 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…While genomic analyses of mammalian tumor-derived cell lines (e.g. Wang et al 2006) have confirmed that the cells often retain global similarities to their tissues of origin, those studies have not pursued the cell-by-cell distinctions made possible here by comparison to a large developmental literature on imaginal discs.…”
Section: Discussionmentioning
confidence: 94%
“…While genomic analyses of mammalian tumor-derived cell lines (e.g. Wang et al 2006) have confirmed that the cells often retain global similarities to their tissues of origin, those studies have not pursued the cell-by-cell distinctions made possible here by comparison to a large developmental literature on imaginal discs.…”
Section: Discussionmentioning
confidence: 94%
“…(33) but is modified in three important ways. The first modification is that we use Spearman's rank correlation rather than Pearson product moment correlation to measure gene expression similarity.…”
Section: Resultsmentioning
confidence: 99%
“…Our choice of a rank-based classifier is motivated by the fact that the rank value of a probe’s expression level within a sample is insensitive to standard within-sample preprocessing methods and is not directly affected by other probes or samples on the array, whereas the expression value is highly dependent on the pre-processing and normalization methods used and can be affected by additional probes and samples (e.g., when robust multichip average (RMA) normalization is used). The second modification is that instead of measuring similarity based on a sample’s global gene expression profile (i.e., the expression levels of all common microarray probes) as used previously (33), we measure similarity based on gene signatures appropriate for the microarray data sets under study and the phenotype of interest (Figure 1C). For tissue alignment, because bladder samples (N=350) were both formalin fixed, paraffin embedded (FFPE) and fresh frozen (FF) (Supplementary Table S2), the gene signature used consists of 12,402 probes whose expression values were preserved across FF and FFPE (24).…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of publicly available TCGA kidney tumours with CCLP and CCLE data for kidney cell lines, we have sub-classified commercially available RCC cell lines into their likely respective RCC sub-histologies; clear cell or papillary (none of the cell lines matched the chromophobe subtype). Previous studies have confirmed that certain RCC cell lines are truly derived from kidney tumours536 and others have categorized them into generic subgroups based on molecular signatures37. However, none of the previous analyses investigated which particular RCC subtype these cell lines originate from.…”
Section: Discussionmentioning
confidence: 99%